Safety on the school bus - Raatma, Lucia; Finkel, Karen E. (Mankato, Minn. : Bridgestone Books, 1999)
Explains how to be safe while waiting for, getting on and off, and riding the school bus.
Includes bibliographical references (p. 24) and index.
Keywords: School children -- Transportation -- Safety measures -- Juvenile literature; School buses -- Safety measures -- Juvenile literature; School buses; Safety